Profile of Nutritional Status Based on Chemotherapy Regimen and Cycle in Colorectal Cancer Patients at Dr. Mohammad Hoesin Hospital Palembang - Muhammad, Fadhil; Manawan, Efman E.U.; Kurniati, Ardesy Melizah; Komar, Muhammad Hafidh; Lusiana, Evi; Adenina, Syarinta (Fakultas Kedokteran Universitas Sriwijaya, 2025)
A cancerous growth that develops from the colon's or rectum's epithelial tissue is called colorectal cancer. Chemotherapy is one of the interdisciplinary approaches used to treat colorectal cancer. Chemotherapy is administered in cycles of one to eight. One of the many adverse consequences of chemotherapy is a decline in nutritional status. In this study, colon cancer patients receiving chemotherapy at Dr. Mohammad Hoesin Hospital Palembang will have their nutritional status described using BMI. It was a descriptive investigation. The most recent medical records of colorectal cancer patients who visited Dr. Mohammad Hoesin Hospital Palembang for chemotherapy were used to gather data. Of the 44 patients, the majority were equally male and female (50%), middle-aged (52.3%), had colon cancer (50%), were in stage IV (75%), had undergone chemotherapy cycle 2 (34.1%), were on the FOLFOX 6 regimen (27.3%), and were well-nourished (50%). The majority of the study's patients were normoweight individuals, undergoing chemotherapy cycle 2, and were on the FOLFOX 6 regimen.